Dynamic Representation-Aided Discovery Learning to Improve Translational Ability between Different Representations at the Same Level - Andrian Saputra; Lisa Tania; Annisa Hanun (Bulletin of Social Studies and Community Development, 2024)
Abstract: This research aimed to describe the effectiveness of discovery learning assisted by molecular simulations in improving translational ability at the same level on stoichiometric topic. The method used in this research was quasi-experimental with purposive sampling data collection techniques. The population in this study were all students in class XI Science at SMA Negeri 2 Metro for the 2022/2023 academic year. Class X IPA 2 was the experimental class while class XI IPA 3 as the control class. The increase in translational ability at the same level was measured based on the significant difference in the n-gain average in the experimental class and the control class. The research results showed that the n-gain average of students in the experimental class was 0.6 in high criteria, while the n-gain average of students in the control class was 0.53 in medium criteria. Based on the difference test, the translational ability at the same level of students in the experimental class was higher than in the control class. It can be concluded that discovery learning assisted by molecular simulations was effective in improving translation abilities at one level of chemical representation in stoichiometric topic. Keywords: discovery learning, molecular simulation, translation ability at one level chemical representation, stoichiometry